Deletion of ferritin H in neurons counteracts the protective effect of melatonin against traumatic brain injury‐induced ferroptosis. Issue 2 (29th November 2020) - Rui, Tongyu; Wang, Haochen; Li, Qianqian; Cheng, Ying; Gao, Yuan; Fang, Xuexian; Ma, Xuying; Chen, Guang; Gao, Cheng; Gu, Zhiya; Song, Shunchen; Zhang, Jian; et al.
Abstract: Accumulating evidence demonstrates that ferroptosis may be important in the pathophysiological process of traumatic brain injury (TBI). As a major hormone of the pineal gland, melatonin exerts many beneficial effects on TBI, but there is no information regarding the effects of melatonin on ferroptosis after TBI. As expected, TBI resulted in the time‐course changes of ferroptosis‐related molecules expression and iron accumulation in the ipsilateral cortex. Importantly, we found that treating with melatonin potently rescued TBI induced the changes mentioned above and improved functional deficits versus vehicle. Similar results were obtained with a ferroptosis inhibitor, liproxstatin‐1. Moreover, the protective effect of melatonin is likely dependent on melatonin receptor 1B (MT2). Although ferritin plays a vital role in iron metabolism by storing excess cellular iron, its precise function in the brain, and whether it involves melatonin's neuroprotection remain unexplored. Considering ferritin H (Fth) is expressed predominantly in the neurons and global loss of Fth in mice induces early embryonic lethality, we then generated neuron‐specific Fth conditional knockout ( Fth ‐KO) mice, which are viable and fertile but have altered iron metabolism. In addition, Fth ‐KO mice were more susceptible to ferroptosis after TBI, and the neuroprotection by melatonin was largely abolished in Fth‐ KO mice. In vitro siFth experiments further confirmed the results mentioned above. Taken together, these data indicate that melatonin produces cerebroprotection, at least partly by inhibiting neuronal Fth‐ mediated ferroptosis following TBI, supporting the notion that melatonin is an excellent ferroptosis inhibitor and its anti‐ferroptosis provides a potential therapeutic target for treating TBI.